Numerical analysis of stress-induced and concentration-dependent carbon diffusion in low-temperature surface carburisation of 316L stainless steel. (14th August 2019) - Peng, Yawei; Gong, Jianming; Jiang, Yong; Rong, Dongsong; Fu, Minghui
A kinetic model based on stress-induced and concentration-dependent carbon diffusion was developed for simulating the carbon concentration-depth profile of carburised austenitic stainless steel. The model considers that the carbon diffusivity is dependent of carbon concentration and the stress induced by diffusion of the dissolved carbon atoms can affect the diffusion behaviour in turn. The results show that in carburised 316L stainless steel, the calculated carbon concentration-depth profile is in good agreement with experimental results, which indicates that the stress and concentration-dependent diffusivity play important roles in carbon diffusion. As a result of carburisation, large compressive residual stress is generated and gradiently distributes in the carburised layer, meanwhile, the diffusion of carbon atoms can be accelerated by stress. Although, the compressive residual stress is not the dominant reason for total carbon diffusivity increases significantly with increasing carbon concentration, as the next driving force it cannot be ignored during low-temperature surface carburisation.